2015
DOI: 10.1590/2317-1545v37n3149041
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the assessment of isoenzymes activity in sunflower seeds

Abstract: -Enzyme activity detection in seeds allows the assessment of the deterioration process in the early stages. In this context, the objective was to assess the effectiveness and the degree of similarity between the results of izoenzymes activity using different methods, as follows: spectrophotometry, visual analysis after electrophoresis, evaluation of the bands nodes gels with software GelAnalyzer. 250 hybrid seeds were submitted to artificial aging to form four lots with differences in physiological quality. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In our study, we were unable to demonstrate differences in SOD activity in platelet lysates, and this failure may have been due to the fact that the concentration of SOD in this blood component is approximately 1 fg of SOD per platelet with 77% in the Cu/Zn isoform, while the rest is in the Mn-SOD isoform, and this is insufficient for evaluation by zymography. However, Faria et al [ 31 ] evaluated the enzymatic activity of SOD using two different techniques and concluded that there were differences in the evaluation results of SOD activity as well as alcohol dehydrogenase between the two methodological techniques used. Better sensitivity of enzymatic evaluations by spectrophotometric techniques was reported [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we were unable to demonstrate differences in SOD activity in platelet lysates, and this failure may have been due to the fact that the concentration of SOD in this blood component is approximately 1 fg of SOD per platelet with 77% in the Cu/Zn isoform, while the rest is in the Mn-SOD isoform, and this is insufficient for evaluation by zymography. However, Faria et al [ 31 ] evaluated the enzymatic activity of SOD using two different techniques and concluded that there were differences in the evaluation results of SOD activity as well as alcohol dehydrogenase between the two methodological techniques used. Better sensitivity of enzymatic evaluations by spectrophotometric techniques was reported [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Faria et al [ 31 ] evaluated the enzymatic activity of SOD using two different techniques and concluded that there were differences in the evaluation results of SOD activity as well as alcohol dehydrogenase between the two methodological techniques used. Better sensitivity of enzymatic evaluations by spectrophotometric techniques was reported [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gels were exposed to white light and immersed in water until the bands corresponding to the SOD bands became visible. Since there are differences between measurements of enzymatic activities ( Faria et al, 2015 ), in the case of SOD we prefer to use the electrophoretic method to the enzymatic one.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the higher resistance to heat, drought and cold than most of the species grown in Brazil (Lima et al, 2014), sunflower areas expanded with about 25% in 2014/2015 as compared to the agricultural year of 2013/2014 (CONAB, 2015). This crop has received more attention due to its good results as an option to succession planting and crop rotation, animal feed, honey production and functional human nutrition (Faria et al, 2015;Ungaro et al, 2009). Furthermore, since 2010, the Brazilian government demands that all diesel commercialized in Brazil should be admixed with at least 5% of biodiesel (Matsumoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%